Evaluating antioxidant and anti-inflammatory activities of Dracaena cambodiana Pierre ex Gagne extracts on RAW 264.7 and SW 1353 cell lines - Huynh Cong Duy; Nguyen Trung Quynh Nhu; Mai Kieu Tien; Nguyen Phuc Thinh; Nguyen Thi Le Thuy; Le Thi Truc Linh; Tran Thi Van Anh; Pham Thi Kim Tram (Vietnam Journal of Science, Technology and Engineering, 2024)
Dracaenae cambodianae Pierre ex Gagnep (Huyet Giac in Vietnamese) is widely utilised in traditional remedies to alleviate joint pain. Indeed, D. cambodianae contains chemical components with biological properties such as cytotoxicity, antimicrobial, and antioxidant activities. This research aims to determine the antioxidant and antiinflammatory properties of D. cambodianae extract in RAW 264.7 and SW 1353 cell lines. The D. cambodianae was extracted with two solvents: dichloromethane (HGA) and methanol (HGB) and subsequently assessed for the total polyphenols and flavonoids content before evaluating its antioxidant and anti-inflammatory properties in RAW 264.7 and SW 1353 cell lines. The extract with HGB exhibited 1.73 times higher total polyphenol content than HGA. The antioxidant capacity (EC50) of HGA was lower than that of HGB. HGA displayed significant cytotoxicity towards the cells, while HGB did not induce cell death. HGB effectively inhibited nitric oxide production, LPS-induced iNOS, and IL-1β-stimulated MMP13 expression. These findings demonstrate that HBG derived from D. cambodianae Pierre ex Gagnep possesses antioxidant and anti-inflammatory properties, offering potential applications in the treatment of inflammation and osteoarthritis in the future.